Iran’s Drone Supply to Russia and Changing Dynamics of the Ukraine War - Mohammad Eslami (Journal for Peace and Nuclear Disarmament, 2022)
The Ukraine war has brought into sharper prominence the importance of drones in modern conflicts. In February 2022, Russia invaded Ukraine, which, contrary to Russia’s expectations, was neither short nor effortless. Relying on Unmanned Combat Aerial Vehicles (UCAV), Ukraine managed to repel many attacks and even destroy Russian armaments in the initial stages of the war. Russia has revealed a certain weakness in the field of unmanned technology, namely drones, and therefore, displaying the urgent need to enlarge its UCAVs fleet increasingly indispensable to Russia’s military operations. In the summer of 2022, Iran transferred hundreds of military drones to Russia in an attempt to ameliorate its lackluster drone capability. The present paper, while describing the role of combat drones in the Ukraine war, elucidates how Iranian UCAVs have been influencing the dynamics of the war in Ukraine.